Foreign Language Absorption For Elementary Students Through English Narrative Text - Indrawati Pusparini; Ike Dian Puspita Sari (Paradigma: Jurnal Filsafat, Sains, Teknologi, dan Sosial Budaya, 2023)
The use of narrative text is used to increase understanding of English for elementary students who participate in this joint learning activity. The use of learning materials in schools is also used to help students better understand the lessons in their schools. The results of observations made by the author before starting research show that students lack motivation in learning English because they rarely use it actively in everyday life. Therefore, activities are filled with involving motoric activities that can attract their attention. The results of the activities were very positive, including students becoming more active language learners, having good learning motivation, and being confident in using simple English expressions to their peers.